Effects of motivational adaptive instruction on motivation towards mathematics learning among lower secondary school students - Wong, Shu Ling (2018)
This quasi-experimental study sought to investigate effects of the motivational adaptive instruction (MAI) on students’ motivation towards mathematics among lower secondary students in a technology-enhanced learning context. A mathematics motivational adaptive instructional approach was designed in accordance with the Attention, Relevance, Confidence, and Satisfaction (ARCS) motivational model to improve students’ motivation towards mathematics learning. Geometer’s Sketchpad (GSP) was utilised in the study to foster a technology-enhanced learning environment. In this study, the motivation construct was constituted of four components, which were attention, relevance, confidence, and satisfaction. This study also determined the effectiveness of the MAI on retaining students’ motivation in learning mathematics. Non-equivalent control group design with pre-test, posttest, and delayed-posttest was adapted for the study. Two intact groups of Malaysian Form Two students were randomly assigned to either an experimental group or a comparison group. There were 20 students in each group and therefore 40 students were involved in the study. The treatment period was two weeks, and a delayed-posttest was conducted two weeks after the treatments were completed. Further, the Course Interest Survey (CIS) was used to measure students’ motivation which includes students’ attention, relevance, confidence, and satisfaction towards mathematics. The study yielded highly reliable and reliable internal consistency for the instrument at pre-test, posttest, and delayed-posttest. Analysis of Covariance (ANCOVA) was conducted to investigate the effects of the motivational adaptive instruction on students’ motivation towards mathematics while students’ pre-test scores were taken as covariate. There were no significant differences in overall motivation (F (1, 37) =1.58, p > .05), attention (F (1, 37) = .38, p > .05), relevance (F (1, 37) = .02, p > .05), and confidence (F (1, 37) = .07, p > .05) mean scores between the experimental and comparison groups after pre-test scores were controlled. However, ANCOVA showed there was a significant difference in students’ satisfaction towards mathematics learning, F (1, 37) = 5.23, p < .05, between the experimental and comparison groups after the covariate was controlled. Paired t tests were conducted to compare the means of posttest and delayed-posttest to assess if there was retention of motivation two weeks after the treatments were completed. The absence of significant difference in motivation indicated that motivation towards mathematics were retained. However, the results should be interpreted with caution due to insignificant effects of the intervention on the constructs. The findings imply that the motivational strategies were not likely to improve students’ overall motivation significantly, but the strategies did enhance students’ satisfaction in mathematics learning. This study supports the efficiency on the motivational strategies in the ARCS model to improve students’ satisfaction toward mathematics in a technology-enhanced learning context. The findings imply that integration of technology in the learning process does not necessarily enhance motivation. The features of technology should be well understood and utilised with appropriate motivational strategies to enhance motivation in the classroom. This study strengthens the idea that teacher is a stimulus that is able to stimulate positive reactions towards a particular classroom or lesson. It is concluded that more time and constructive effort are required to advance students’ motivation while positive stimuli can be conditioned to help students anticipate mathematics lessons.